Distribution and risk assessment of nutrients and heavy metals from sediments in the world-class water transfer projects - Feng, Weiying; Tao, Yingru; Liu, Minjie; Deng, Yuxin; Yang, Fang; Liao, Haiqing; Li, Tingting; Song, Fanhao; Ngien, S. K. (Springer, 2024)
South-to-North Water Diversion Project, a globally renowned engineering feat, aims to address water supply issues. The sediments within reservoirs play a pivotal role in natural ecosystems, not only as habitats for diverse biota but also as repositories of heavy metals, organic matter, and other contaminants. These sediments serve as a critical interface between sediment and water bodies. This comprehensive analysis focused on the spatial patterns of nutrients, organic matter, and heavy metals in the surface layer and profiles of reservoirs, exploring their interconnectedness. Leveraging the integrated pollution index, organic pollution index, potential ecological risk index, and geo-accumulation index, an ecological risk assessment was performed. The key findings are as follows: (i) Along the Middle Route of the South-to-North Diversion Project, the nutrient and organic matter contents in sediments tends to rise with distance from the Danjiangkou Reservoir, with the TN and TC contents increasing by 2.35- and 3.05-fold, respectively. (ii) As the sediment depth increases, the carbon, nitrogen, phosphorus, and organic matter contents exhibit varying degrees of decline, with average decreases of 62.38%, 67.47%, 17.56%, and 41.83% for TN, TC, TP, and OM, respectively. (iii) Among the eight heavy metals, only manganese (Mn) and zinc (Zn) in the Yahekou Reservoir showed moderate pollution levels, according to the geo-accumulation index. The Mn content within the surface sediments of the six reservoirs ranges from 550 to 1837 mg/kg (average, 1019.5 ± 548.3 mg/kg), whereas the Zn content ranges from 89 to 360 mg/kg (average, 156.5 ± 101.6 mg/kg). (vi) Total phosphorus (TP) and total nitrogen (TN) emerged as the primary pollutants in surface sediments. Comprehensive nitrogen and phosphorus pollution assessment revealed that the surface sediment of Danjiangkou Reservoir is mildly polluted, while Baiguishan and Jiangang Reservoirs are moderately polluted, and the rest are heavily contaminated. For the Yahekou and Chaohe Reservoirs, the average pollutant content indicates moderate pollution, while the remaining reservoirs show mild pollution levels. Graphical Abstract: (Figure presented.)